STEAM AS AN INNOVATIVE TECHNOLOGY IN TEACHING ENGLISH - Irgasheva Umida Raimjanovna (Bright Mind Publishing, 2025)
The article explains the STEAM (Science, Technology, Engineering, Arts and Mathematics) as an innovative technology in teaching English as a foreign language. It proves how incorporating STEAM technologies into English lessons can provide a holistic learning experience that fosters creativity, critical thinking, and interdisciplinary connections. Some ways how to integrate STEAM technologies into English lessons are shown here. The basis of modern approaches, the suggestions and recommendations for enhancing the information methodological support for the development of communicative, linguistic, sociolinguistic, pragmatic, speech and lexical competences with the help of STEAM technologies in teaching English are explained in the article.
Keywords: Innovative, motivation, creative, collaborative, digital, communicate, integrate, unique, encourage, challenge, teamwork.